Single synchronous delivery of FK506-loaded polymeric microspheres with pancreatic islets for the successful treatment of streptozocin-induced diabetes in mice. (1st January 2017) - Pathak, Shiva; Regmi, Shobha; Gupta, Biki; Poudel, Bijay K.; Pham, Tung Thanh; Yong, Chul Soon; Kim, Jong Oh; Kim, Jae-Ryong; Park, Min Hui; Bae, Young Kyung; Yook, Simmyung; Ahn, Cheol-Hee; et al.
Abstract: Immune rejection after transplantation is common, which leads to prompt failure of the graft. Therefore, to prolong the survival time of the graft, immunosuppressive therapy is the norm. Here, we report a robust immune protection protocol using FK506-loaded microspheres (FK506M ) in injectable hydrogel. Pancreatic islets were codelivered with the FK506M into the subcutaneous space of streptozocin-induced diabetic mice. The islets codelivered with 10 mg/kg FK506M maintained normal blood glucose levels during the study period (survival rate: 60%). However, transplantation of islets and FK506M at different sites hardly controlled the blood glucose level (survival rate: 20%). Immunohistochemical analysis revealed an intact morphology of the islets transplanted with FK506M . In addition, minimal number of immune cells invaded inside the gel of the islet-FK506M group. The single injection of FK506M into the local microenvironment effectively inhibited immune rejection and prolonged the survival time of transplanted islets in a xenograft model.